1977
DOI: 10.1073/pnas.74.12.5702
|View full text |Cite
|
Sign up to set email alerts
|

Cultured aortic endothelial cells from pigs with von Willebrand disease: in vitro model for studying the molecular defect(s) of the disease.

Abstract: vWd that resembles the classic disease in man has also been described in dogs (5) and pigs (5, 6). The purpose of this communication is to describe the long-term culture and properties of normal and vWd porcine endothelial cells and the use of this in vitro culture system for studying the molecular defect(s) in vWd.MATERIALS AND METHODS Preparation and Culture of Cells. No detectable Willebrand factor or RWF could be demonstrated in the plasma of the vWd pigs that were used as the source of vWd aortas. Willebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1980
1980
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…Weiss et al [35] have demon strated that the defect of adhesion of human von Willebrand platelets to a-chymotrypsintreated rabbit SE could be corrected by the addition of F. VIII. We have previously dem onstrated that pretreatment of cultured por cine aortic ECs (damaged by scraping) with monospecific chicken antiporcine F. VIIIR:WF serum completely abolished the interaction of platelets with exposed SE ma terial [8]. We have also demonstrated that the decreased interaction of platelets with SE from cultured von Willebrand porcine aortic ECs may be due to the decreased and/or abnormal distribution of immunologically identifiable F. VIIIR:WF-containing micro filaments in the SE of these von Willebrand ECs [8][9][10], Finally, the localization, by im munofluorescence staining, of F. VIIIR:AG in human vascular SE has recently been re ported [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Weiss et al [35] have demon strated that the defect of adhesion of human von Willebrand platelets to a-chymotrypsintreated rabbit SE could be corrected by the addition of F. VIII. We have previously dem onstrated that pretreatment of cultured por cine aortic ECs (damaged by scraping) with monospecific chicken antiporcine F. VIIIR:WF serum completely abolished the interaction of platelets with exposed SE ma terial [8]. We have also demonstrated that the decreased interaction of platelets with SE from cultured von Willebrand porcine aortic ECs may be due to the decreased and/or abnormal distribution of immunologically identifiable F. VIIIR:WF-containing micro filaments in the SE of these von Willebrand ECs [8][9][10], Finally, the localization, by im munofluorescence staining, of F. VIIIR:AG in human vascular SE has recently been re ported [24].…”
Section: Discussionmentioning
confidence: 99%
“…Platelets were obtained from freshly drawn porcine blood containing ACD (38 m M citric acid -75 mM sodium citrate -125 m M dextrose) as anticoagulant; 1 ml of ACD/8 ml of blood and washed as described previously [8]. The platelet pellet was finally resus pended in modified TBSS at a cell concentration of 4 X 105 platelcts/mm5.…”
Section: Preparation O F Washed Plateletsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most cultured endothelial cells retain the features of endotheliumii in vivo, including an epithelioid shape an(V Weibel-Palade bodies in the cytoplasm (25)(26)(27). Factor VIII antigen is associated with cells fromn human veins (12,15) and with cells from aortas of animials (19,21,24). Angiotensin I convertinig enzyme activity is found in cells from umbilical cord veins (15,16) and also in aortic endothelial cells from various species (20,28,29).…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial cells have been cultured from veins of human umiibilical cords (12)(13)(14)(15)(16), vena cavae of rabbits (17), andI large arterial vessels of pigs (18)(19)(20) and cows (21)(22)(23)(24). Most cultured endothelial cells retain the features of endotheliumii in vivo, including an epithelioid shape an(V Weibel-Palade bodies in the cytoplasm (25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%